Changes of left ventricular mechanics after trans-catheter aortic valve implantation and surgical aortic valve replacement for severe aortic stenosis: A tissue-tracking cardiac magnetic resonance study. (1st February 2017) - Nucifora, Gaetano; Tantiongco, John-Paul; Crouch, Gareth; Bennetts, Jayme; Sinhal, Ajay; Tully, Phillip J.; Bradbrook, Craig; Baker, Robert A.; Selvanayagam, Joseph B.
Abstract: Background: Left ventricular (LV) mechanics are impaired in patients with severe aortic stenosis (AS). The aim of the present study was to assess their changes early and late after trans-catheter aortic valve implantation (TAVI) and surgical aortic valve replacement (AVR) using cardiac magnetic resonance (CMR) tissue-tracking imaging. Methods: In 59 patients with severe AS undergoing either TAVI ( n  = 35) or surgical AVR ( n  = 24), CMR with late gadolinium enhancement (LGE) imaging was performed before and early post-procedure to evaluate LV function and mass, and presence/extent of LGE. A third CMR scan was performed in 29 patients after a mean follow-up of 15 ± 4 months. Tissue-tracking analysis was applied to cine CMR images, to assess LV global longitudinal (GLS), circumferential (GCS) and radial (GRS) strains. Results: The TAVI and surgical AVR groups were similar with respect to baseline ( p  = 0.14) and early post-procedure ( p  = 0.16) LV ejection fraction. However, baseline LV GLS was significantly impaired in TAVI patients compared to surgical AVR patients ( p  = 0.025). Early post-procedure, TAVI resulted in a significant improvement of LV GLS ( p  = 0.003), while a significant worsening of LV GLS was observed early after surgical AVR ( p  = 0.012). At longer term follow-up, both TAVI and surgical AVR groups experienced a significant reduction of LV mass and a significant improvement of LV myocardial mechanics in all the three directions. Conclusions: Treatment-specific differences in the changes of LV myocardial mechanics early after afterload release by TAVI and surgical AVR are present. Later, both interventions are associated with an improvement of LV myocardial deformation, alongside a regression of LV hypertrophy.